Dynamical Complexity Fingerprints of Occupation-Dependent Brain Functional Networks in Professional Seafarers - Yan, Hongjie; Wu, Huijun; Chen, Yanyan; Yang, Yang; Xu, Min; Zeng, Weiming; Zhang, Jian; Chang, Chunqi; Wang, Nizhuan (Frontiers in Neuroscience, 2022)
The complexity derived from the resting-state functional magnetic resonance imaging (rs-fMRI) data has been applied for exploring cognitive states and occupational neuroplasticity. However, there is little information about the influence of occupational factors on dynamic complexity and topological properties of the connectivity networks. In this paper, we proposed a novel dynamical brain complexity analysis (DBCA) framework to explore the changes in dynamical complexity of brain activity at the voxel level and complexity topology for professional seafarers caused by long-term working experience. The proposed DBCA is made up of dynamical brain entropy mapping analysis and complex network analysis based on brain entropy sequences, which generate the dynamical complexity of local brain areas and the topological complexity across brain areas, respectively. First, the transient complexity of voxel-wise brain map was calculated, compared with non-seafarers, seafarers showed decreased dynamic entropy values in the cerebellum and increased values in the left fusiform gyrus (BA20). Further, the complex network analysis based on brain entropy sequences revealed the small-worldness in terms of topological complexity in both seafarers and non-seafarers, indicating that is an inherent attribute of human brain. In addition, seafarers showed higher average path length and lower average clustering coefficient than non-seafarers, suggesting that the information processing ability is reduced in seafarers. Moreover, the reduction in efficiency of seafarers suggests that they have less efficient processing network. To sum up, the proposed DBCA is effective to explore the dynamic complexity changes at voxel-wise activity and region-wise connectivity, showing that occupational experience can reshape seafarers’ dynamic brain complexity fingerprints.